The Monstrous Flesh: collective bodies and the State-Form in Modern Mesopotamia - Ganji, Iman (Revista Brasileira de Estudos da Presença, 2022)
The Middle East is in chaos. Having been described as monstrous, the Islamic State (ISIL) has been defeated only to come back as a chronic guerrilla style insurgency and the shadow of further conflicts that are still looming in the region. The following article takes up this situation through the concept of the biopolitical monster as the common body of resistance and struggle, exploring the liberatory aspects of this concept in terms of organization and political autonomy, and argues that ISIL has more in common with the State-form than with the monstrous. Discussing the colonial and neo-colonial aspects of the situation, the case of Kurdish Northern Syria will be presented in contrast to the ISIL. It continues to argue for a social monstrous flesh as the performative body of contemporary protest movements, tracing back the rhizomatic etymologies of monster to Aristotle and early Islamic philosophers, drawing inspirations mainly from the tradition of immanent thought and its contemporary thinkers such as Foucault, Deleuze, Guattari, and Negri.